Unsur-Unsur Kebahagiaan Menurut Imam Al-Ghazali dalam Kitab Kimiya’ Al-Sa’adah - Aulianda, Atika (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
This research examines the Elements of Happiness According to Imam Al-Ghazali in the Book of Kimiya’ Al-Sa’adah. Al-Ghazali is a prominent philosopher who was born in the Khurasan area, al-Ghazali is known as a divine expert and a great philosopher. Besides that, he was also famous as a jurist and tasawwuf expert who had no equal at that time, so that his writings in the form of the book Ihya’ U’lum al-Din provided motivation to mankind in achieving happiness both in this world and in the hereafter. The goal to be achieved is to find out the method of achieving happiness according to Imam al-Ghazali. The author uses a qualitative approach through a research process with library research, because all data obtained from studies or reviews of books, scientific papers, journals, and some other literature is related to the issues discussed. By using a descriptive analysis method sourced from primary data, namely al-Ghazali’s work entitled Kimiya’ al-sa’adah, and secondary data related to happiness in al-Ghazali’s view. The results of this study can be concluded that the method offered by al-Ghazali in achieving happiness through his work Kimiya’ al-sa’adah consists of eight important elements in it, namely, first knowing yourself. Second, know God. Third, get to know the world. Fourth, know the hereafter. Fifth, spiritual in music and dance. Sixth, muhasabah and remembrance. Seventh, marriage. Eighth, love to Allah SWT.